2021
DOI: 10.1111/jcpt.13410
|View full text |Cite
|
Sign up to set email alerts
|

The outcomes and acceptance of pressurized metered‐dose inhaler bronchodilators with venturi mask modified spacer in the outpatient emergency department during the COVID‐19 pandemic

Abstract: What is known and objective Nebulizer use has been suspended in Malaysian public health facilities due to the potential to aggravate COVID‐19 nosocomial transmission. Currently, our facility uses the pressurized metered‐dose inhaler (pMDI) bronchodilator with Venturi mask modified spacer (VMMS) in patients visiting the Emergency Department (ED) for mild to moderate exacerbation of asthma and chronic obstructive pulmonary disease (COPD). We sought to assess the outcomes and acceptance of pMDI‐VMMS in the outpat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…In various developing countries, commercial spacers with facemask are not readily accessible due to the high cost and lack of availability, particularly as the pandemic has led to a sharp increase in demand. Despite their high price, many of these therapies are not designed for re-use with other patients due to cross-infection risk ( 33 ). However, extraordinary times call for extraordinary actions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In various developing countries, commercial spacers with facemask are not readily accessible due to the high cost and lack of availability, particularly as the pandemic has led to a sharp increase in demand. Despite their high price, many of these therapies are not designed for re-use with other patients due to cross-infection risk ( 33 ). However, extraordinary times call for extraordinary actions.…”
Section: Introductionmentioning
confidence: 99%
“…Another modality deployed during the pandemic in place of nebulisers and commercial spacers is the use of pMDI with the Venturi mask modified spacer (VMMS). A local study on its use in the Hospital Kuala Lumpur’s outpatient emergency department found that SABA delivered through VMMS appeared be equivalent to nebulisers in terms of efficacy, was well-accepted by patients and staff members, and offered a more cost-effective alternative to commercial spacers ( 33 ). Therefore, as resource can be the limiting factors for many healthcare facilities during this difficult times, homemade spacers and VMMS serve as efficient and promising options.…”
Section: Introductionmentioning
confidence: 99%